PENTINGNYA INTEGRASI NILAI-NILAI PRIBADI, KELUARGA DAN MASYARAKAT UNTUK MEWUJUDKAN KEHARMONISAN SOSIAL - Amanah, Nurul; Jannah, Dina Rohmatul; Misun (Journal of Islamic Studies, 2025)
This study explores the integration of personal, family, and societal values in fostering social harmony. Personal values such as honesty, responsibility, and integrity form the foundation of an individual's character, influencing their decisions and interactions. Family values, including affection, respect, and cooperation, play a crucial role in shaping moral standards through interactions within the household. Societal values like justice, equality, and tolerance are essential for maintaining social order and promoting peace in diverse communities. The research method is Systemathic Literature Review. The study emphasizes the importance of aligning these values to strengthen individual identity, enhance social cohesion, and optimize social roles, leading to a more harmonious and just society. The paper also identifies challenges such as value conflicts, generational differences, and social changes that hinder value integration and proposes strategies like intergenerational dialogue, value-based education, and community involvement to overcome these obstacles. Ultimately, the integration of values contributes to building a sustainable, inclusive, and compassionate society, where individuals are motivated to contribute to collective well-being.